An investigation into the system of theme and rheme in electronic news headlines: the case of BBC news headlines = Cấu trúc đề thuyết trong tiêu đề báo điện tử - Nghiên cứu trường hợp tiêu đề báo điện tử BBC. M.A. Thesis Linguistics: 60 22 15 - Nguyễn, Thị Nguyệt Minh (University of Languages and International Studies, 2017)
M.A. Thesis English Linguistics -- University of Languages and International studies. Vietnam National University, Hanoi, 2011